Levando a imparcialidade a sério: proposta de um modelo interseccional entre direito processual, economia e psicologia - Costa, Eduardo José da Fonseca (2016)
Impartiality is essential to jurisdiction, and among other things, it guarantees the parties and the maintenance of democracy itself. The procedural law systems currently in force in Brazil need to walk in opposite direction to the path they are actually taking in order for it to be minimally guarded, that is, regarding subjective impartiality specifically. These systems have already been feeding the cognitive bias factors of the adjudicative decision-makers and, therefore, feeding a breach of its systemic and unconscious biases. In this sense, the present work proposes a legislative reform, offering a precautionary model of lege ferenda inspired in algorithmic strategies based on the latest findings of a new discipline increasingly thriving in Anglo-Saxon countries, Israel and Western Europe called Behavioral Law and Economics (resulting from a fusion of law, cognitive psychology and behavioral economics). Hence the reason it is a legal enginnering work. Now, assuming that any decision maker is equipped with a bounded rationality (not to be confused with actual irrationality ), these techniques seek to undo or to isolate the effects of the so-called cognitive biases , which are mere shortcuts predictable and therefore, preventable which the human mind develops in order to make decisions from complex information under situations of uncertainty. Thus, the major cognitive illusions which affect the adjudicative decision-makers (representativeness bias, anchoring-and-adjustment bias, confirmation bias and in-group bias) were studied along with the procedural standards better suited to neutralize or eliminate these biases. Nevertheless, the proposed model is open to new discoveries that may occur regarding this matter. However, even in the case of a lege ferenda model, one can from it criticize de lege lata of the Brazilian Positive Law and demonstrate that many of the common biased practices in daily forensic activities could have already been confronted